Joint Source-Channel Codes for MIMO Block Fading Channels - Gunduz,D; Erkip,E (IEEE Transactions Information Theory, 2008)
We consider transmission of a continuous amplitude source over an L-blockRayleigh fading $M_t × M_r$ MIMO channel when the channel stateinformation is only available at the receiver. Since the channel is notergodic, Shannon's source-channel separation theorem becomes obsolete and theoptimal performance requires a joint source -channel approach. Our goal is tominimize the expected end-to-end distortion, particularly in the high SNRregime. The figure of merit is the distortion exponent, defined as theexponential decay rate of the expected distortion with increasing SNR. Weprovide an upper bound and lower bounds for the distortion exponent withrespect to the bandwidth ratio among the channel and source bandwidths. For thelower bounds, we analyze three different strategies based on layered sourcecoding concatenated with progressive, superposition or hybrid digital/analogtransmission. In each case, by adjusting the system parameters we optimize thedistortion exponent as a function of the bandwidth ratio. We prove that thedistortion exponent upper bound can be achieved when the channel has only onedegree of freedom, that is L=1, and $\min\{M_t,M_r\}=1$. When we have moredegrees of freedom, our achievable distortion exponents meet the upper boundfor only certain ranges of the bandwidth ratio. We demonstrate that ourresults, which were derived for a complex Gaussian source, can be extended tomore general source distributions as well.